EFEKTIVITAS PENERAPAN METODE TIKRAR TERHADAP PENINGKATAN HAFALAN DALAM PEMBELAJARAN AL-QUR’AN HADIS DI MADRASAH TSANAWIYAH AT-TARBIYAH ISLAMIYAH KOLAKA - Iswatuna, Iswatuna (IAI Al-Mawaddah Warrahmah Kolaka, 2021)
In the world of teaching and learning process (PBM), the method is much more important than the material. Thus the urgency of the method in the process of education and teaching. A teaching and learning process can be said to be unsuccessful if the process does not use methods. Because the method occupies the second most important position after the objectives of a series of learning components: objectives, methods, materials, media and evaluation. Based on this, this research is about the effectiveness of the tikrar method on improving memorization in learning the Qur'an Hadith at Madrasah Tsanawiyah At Tarbiyah Islamiyah Kolaka. With the formulation of the problem, among others: How is the effectiveness of the Tikrar method in improving memorization in learning the Qur'an Hadith at MTs Pondok Pesantren At-Tarbiyah Islamiyah Kolaka. The purpose of this study was to determine the effectiveness of the Tikrar method in improving memorization in learning the Qur'an Hadith at MTs Islamic boarding school At-Tarbiyah Islamiyah Kolaka. This type of research is a field research with a qualitative descriptive approach. The data sources are Al-Qur'an Hadith educators (teachers), students, the Principal of MTs At-Tarbiyah Islamiyah Kolaka. The method used in data collection is through observation, interviews, and documentation. Then analyzed using data reduction, data presentation, and drawing conclusions, and testing the validity of the data. This study concludes that: The implementation of the tikrar method for the memorization program in learning Al-Qur'an Hadith at MTs At-Tarbiyah Islamiyah Kolaka is carried out in two ways, namely: first, by group or classical. That is, educators (teachers) prepare and read the arguments of the verses of the Qur'an or Hadith in a rather loud voice. Followed by students with a minimum repetition count of 10-20 times. With movement instructions from educators. Second, in an individual way, namely: educators give instructions to students to memorize and deposit the material that has been studied. The effectiveness of the tikrar method is quite effective in increasing the memorization of students in learning Al-Quran Hadith at MTs At-Tarbiyah Islamiyah Kolaka. By looking at the success of students who have the ability, willingness in the memorization process and achieve the minimum mastery learning target.